Oxford handbook of acute medicine - Ramrakha, Punit S.; Moore, Kevin P.; Sam, Amir H. ([Oxford] : Oxford University Press, 2019)
The fourth edition of the Oxford Handbook of Acute Medicine has been revised throughout to include the most up-to-date guidelines and treatment management plans. With new figures and clinical tips, and a brand new chapter on the older patient, this edition remains the must-have resource for all those dealing with acute illness.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 7, 2019).
Keywords: Medical emergencies; Critical care medicine